Maintaining Safety and Facilitating Inclusion: Using Applied Behavior Analysis to Address Self-Injurious Behaviors Within General Education Classrooms. (December 2019) - Robinson, Jason; Gershwin, Tracy; London, Dina
This article provides educators with a research-informed process for addressing student problem self-injurious behaviors within inclusive settings. The process involves (a) identifying functions of problem behaviors, (b) implementing function-based interventions that include teaching and reinforcing socially acceptable replacement behaviors, (c) monitoring student progress and fidelity of implementation, and (d) fading interventions to facilitate long-term success. The process is described in practical detail using a case study vignette about a fifth-grade student who engages in self-injurious behaviors.